2013
DOI: 10.1016/j.foreco.2012.06.055
|View full text |Cite
|
Sign up to set email alerts
|

What causes large fires in Southern France

Abstract: In Southern France, where most wildfires occur, the fire size has never exceeded 6 744 ha since 1991, whereas mega-fires have burned huge areas in other Mediterranean countries such as Spain and Portugal. It was interesting to find out what main factors drove the ignition of the largest fires that had occurred in this region of France.The study was carried out using the forest fires database Prométhée that records all fires occurring in the 15 départements of Southern France since 1973. However, the records pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 60 publications
10
73
0
7
Order By: Relevance
“…"Arrolamento Geral de Gados e Animais de Capoeira" : 1934, 1955and 1970"Recenseamento Agrícola do Continente": 1989, 1999, Instituto Nacional de Estatística of the Piodão and Pomares parishes, respectively) ( Figure 7). Several studies confirm that this land cover is one of the types most seriously affected by wildfires (Nunes et al 2005;Sebastián-López et al 2008;Catry et al 2009;Moreira et al 2009;Bajocco and Ricotta 2008;Nunes 2012;Carmo et al 2011;Oliveira et al 2012;Ganteaume and Jappiot, 2013;Oliveira 2014;Nunes et al 2016). Conversely, Nunes et al (2016) found that in Portugal at municipal level, traditional activities based on agriculture, grazing and forestry seem to reduce the burnt area, suggesting that the survival of Mediterranean silvopasture activities reduces the frequency and impact of forest fires.…”
Section: Social and Economic Changesmentioning
confidence: 97%
“…"Arrolamento Geral de Gados e Animais de Capoeira" : 1934, 1955and 1970"Recenseamento Agrícola do Continente": 1989, 1999, Instituto Nacional de Estatística of the Piodão and Pomares parishes, respectively) ( Figure 7). Several studies confirm that this land cover is one of the types most seriously affected by wildfires (Nunes et al 2005;Sebastián-López et al 2008;Catry et al 2009;Moreira et al 2009;Bajocco and Ricotta 2008;Nunes 2012;Carmo et al 2011;Oliveira et al 2012;Ganteaume and Jappiot, 2013;Oliveira 2014;Nunes et al 2016). Conversely, Nunes et al (2016) found that in Portugal at municipal level, traditional activities based on agriculture, grazing and forestry seem to reduce the burnt area, suggesting that the survival of Mediterranean silvopasture activities reduces the frequency and impact of forest fires.…”
Section: Social and Economic Changesmentioning
confidence: 97%
“…Agricultural abandonment is the main cause of an increased fuel load (Millán et al, 1998), but wildland fuel homogeneity and continuity are also major facilitators of both a fast fire propagation and a higher fire line intensity Vega-García and Chuvieco, 2006). In addition, climate and weather are two of the main factors influencing fire regime (Trouet et al, 2009), and climate change could have an important impact on ecosystems due to increases in area burned and fire intensity/severity (Flannigan et al, 2000). Regato (2008) showed that climate change could provide an increase in the intensity and frequency of summer heat waves (short periods with very hot days, very low air humidity and frequently with strong winds) that increase the probability of large wildland fire (LWF).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, just a few LWFs cause the majority of the damage (Alvarado et al, 1998;Ganteaume and Jappiot, 2012) because they account for a very high percentage of the total burned area (Stocks et al, 2003), and their severity is normally higher. In these LWF events fire behavior is often extreme, making suppression difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although environmental protection and minimization of fire risk should promote the protection of the areas and sites characterized by environmental and/or natural resources, the construction of new roads and pathways, the increment of rural areas and the promotion of rural tourism could potentially generate negative impacts. For example, according to Ganteaume and Jappiot [40], the presence of minor roads and tourism pressure are drivers for the occurrence of large fires and the size of burned areas, respectively. Moreover, we observe, following Burkhard et al [37], that the land use categories, included in the "Mountain of Sette Fratelli" SPA, have a high-to-medium capacity to provide livestock.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we observe, following Burkhard et al [37], that the land use categories, included in the "Mountain of Sette Fratelli" SPA, have a high-to-medium capacity to provide livestock. Furthermore, pastoral activities and pasture may generate negative impacts in relation to habitats' protection (MP of the SPA "Mountain of Sette Fratelli") and fire occurrence [40].…”
Section: Resultsmentioning
confidence: 99%